PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN KOMITMEN MANAJEMEN PUNCAK TERHADAP TRANSFER KNOWLEDGE DAN DAMPAKNYA TERHADAP KINERJA DOSEN - Dwi Antoro (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
The process of globalization has increased the preparation and maturity that is needed in the empowerment of human resources in Indonesia. Because globalization is synonymous with the free competition of a country to be poor or underdeveloped, it is not because of natural resources but poor and underdeveloped due to a lack of qualified human resources. This study aimed to analyze the influence of leadership, organizational culture, and top management commitment to the transfer of knowledge and its impact on performance. The test results on the variables of leadership and knowledge transfer shows that the leadership is not proven significant effect on knowledge transfer. Variable organizational culture and knowledge transfer suggests that organizational culture proved a significant effect on knowledge transfer. Variable top management commitment and knowledge transfer shows that top management commitment shown to significantly influence the transfer of knowledge. Variable leadership and faculty performance shows that leadership proved to have a significant effect on the performance of lecturers. Variable top management commitment and performance of the lecturer shows that top management commitment shown to have a significant effect on the performance of lecturers. The test results on the variable transfer knowledge and performance of the lecturer shows that the transfer of knowledge proved to have a significant effect on the performance of lecturers.Keywords : leadership, organizational culture, performance, and top management commitment